Literaturgeschichte: Theorien - Modelle - Praktiken - Buschmeier, Matthias (Studien und Texte zur Sozialgeschichte der Literatur, 2014)
In recent years, there has been a revival of theoretical debates about the history of literature along with practical ventures in the field of philology. This work surveys the current status of identifiable theoretical problems and discusses new models and concepts for literary historiography
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Literaturgeschichte; Literaturgeschichtsschreibung